Glucosylceramide in bunyavirus particles is essential for virus binding to host cells - Uckeley, Zina Maria; Duboeuf, Maëva; Gu, Yu; Erny, Alexandra; Mazelier, Magalie; Lüchtenborg, Christian; Winter, Sophie L.; Schad, Paulina; Mathieu, Cyrille; Koch, Jana; Boulant, Steeve; Chlanda, Petr; et al. (Cellular and molecular life sciences, 2024)
Hexosylceramides (HexCer) are implicated in the infection process of various pathogens. However, the molecular and cellular functions of HexCer in infectious cycles are poorly understood. Investigating the enveloped virus Uukuniemi (UUKV), a bunyavirus of the Phenuiviridae family, we performed a lipidomic analysis with mass spectrometry and determined the lipidome of both infected cells and derived virions. We found that UUKV alters the processing of HexCer to glycosphingolipids (GSL) in infected cells. The infection resulted in the overexpression of glucosylceramide (GlcCer) synthase (UGCG) and the specific accumulation of GlcCer and its subsequent incorporation into viral progeny. UUKV and several pathogenic bunyaviruses relied on GlcCer in the viral envelope for binding to various host cell types. Overall, our results indicate that GlcCer is a structural determinant of virions crucial for bunyavirus infectivity. This study also highlights the importance of glycolipids on virions in facilitating interactions with host cell receptors and infectious entry of enveloped viruses.
Gesehen am 24.06.2024